Long non‐coding RNA MALAT1/microRNA 125a axis presents excellent value in discriminating sepsis patients and exhibits positive association with general disease severity, organ injury, inflammation level, and mortality in sepsis patients. Issue 6 (20th April 2020) - Liu, Wei; Geng, Feng; Yu, Li
Abstract: Objective: The present study aimed to investigate the potential value of long non‐coding RNA metastasis‐associated lung adenocarcinoma transcript 1 (lnc‐MALAT1)/microRNA (miR)‐125a axis in disease management and prognosis surveillance of sepsis. Methods: Totally, 196 sepsis patients and 196 healthy controls were enrolled. Blood samples were collected within 24 hours after admission in sepsis patients and were collected at enrollment in healthy controls. The relative expression of lnc‐MALAT1 and miR‐125a in all participants was detected by reverse transcription quantitative polymerase chain reaction, and the inflammatory cytokines in plasma of sepsis patients were measured by enzyme‐linked immunosorbent assay. Results: Lnc‐MALAT1/miR‐125a axis was increased in sepsis patients compared with healthy controls ( P  < .001) and was of excellent value in distinguishing septic patients from healthy controls with the area under the curve (AUC) of 0.931 (95% CI: 0.908‐0.954). In sepsis patients, lnc‐MALAT1 was negatively associated with miR‐125a, and lnc‐MALAT1/miR‐125a axis was positively correlated with acute pathologic and chronic health evaluation II (APACHE II) score, Sequential Organ Failure Assessment (SOFA) score, serum creatinine, C‐reactive protein, tumor necrosis factor‐α, interleukin (IL)‐1β, IL‐6, and IL‐8, while negatively associated with albumin. Furthermore, lnc‐MALAT1/miR‐125a axis was of value in predicting increased 28‐day mortality risk to some extent (AUC: 0.678, 95% CI: 0.603‐0.754). Conclusion: Lnc‐MALAT1/miR‐125a axis presents excellent value in differentiating sepsis patients from healthy controls and also exhibits positive association with general disease severity, organ injury, inflammation level, and mortality in sepsis patients.